THE ROLE OF PUBLIC SPEAKING AND EFFECTIVE WAYS TO OVERCOME SPEECH RELATED PROBLEMS - Feruzakhon Mansurova (University Research Base, 2024)
Public speaking is considered to be one of the most important skills a person has to master. This article will introduce the general overview of public speech, the reasons why it has been the demand of all the spheres of our life until current time. It also categorizes the types and principles of public speech and the main speech problems related to speaking in public. According to the problems mentioned, some vital tips to overcome the speech related issues and effective methods to enhance public speech will be given in the statement.